Experiencing the Ancient Indian Healthcare Science of Ayurveda Through the Immersive Experiential Prism of a Scholar from the Global North West Visiting an Ayurveda Centre in Coastal Karnataka - Basavaraj S Hadapad1 , Anupama V Nayak2 , Chaitanya Sanjay Mishra3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Ayurveda is an ancient age-old practice that for many centuries has developed to become the principleteaching of how to live a healthy lifestyle: “Ayurveda, the ancient traditional medicine of India, defines healthas a state of complete physical, mental and spiritual well-being. The focus of Ayurveda is on a predictive,preventive and personalized medicine. This is obtained through low-cost personalized counseling aboutlifestyle measures (diet, activities, etc.), trying to involve the patient directly in the process of healing,increasing his self-awareness and good relationships with other people and nature”. Ayurveda approacheshealth from a holistic perspective. Its goal is not to reduce pain, as most modern medicine does, but to preventit: “The person-centered point of view of Ayurveda mainly concerns the maintenance of an abiding health,preventing rather than treating diseases. If our health is compromised, the treatment resides in restoring thebalance between the affected functions, the tissues, the environment and the whole organism. The nature ofthe individual is a parameter on which the whole system’s scale is tuned.”